Hubungan Pengetahuan dengan Perilaku Masyarakat dalam Membuang Sampah di Sungai Sago Pekanbaru - Suryani, Suryani; Ningsih, Kursiah Warti (Dinamika Lingkungan Indonesia, 2020)
Based on a report by the Directorate General of Pollution and Environmental Damage Control of the Ministry of Environment and Forestry (KLHK), in 2015 nearly 68 percent or the majority of the quality of cistern water in 33 provinces in Indonesia was in a heavily polluted status. The main source of river pollutants is domestic or household waste. Human behavior is the biggest cause of environmental damage. The purpose of this study is to link knowledge with people's behavior in disposing household waste in the Sago River. This type of research is quantitative research with a cross-sectional approach. The independent variable in this study is people's knowledge in disposing household waste. The population in this study were all housewives who lived in the area around the Sago river, as many as 974 people. The samples in this study were 284 people and the sampling technique was Stratified Random Sampling. The instruments used were questionnaires and observation sheets. Primary data obtained through questionnaires and observations while secondary data from Sukaramai Kelurahan Pekanbaru data. Data analysis used chi square test with a = 0.05. The results showed that there was a relationship between knowledge and the behavior of disposing garbage with a value a<0,05. This research would be used for further research, namely to make the right program in handling garbage in the Sago River in Pekanbaru.